Sistem Pencegah Plagiarisme Dalam Tugas Mahasiswa Dengan Snapshotting dan User Activity Logging - Azzam Syawqi Aziz; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Plagiarism is an inseparable thing from an academic environment. Various motivations including working part-time and social dilemmas contribute to the high percentage of plagiarism at the university level. Handling with the plagiarism detection method has many disadvantages, such as the emergence police-criminal paradigm, value-oriented mindset, and technical weakness such as inability in analyzing translated documents. Hellas, Leinonen, and Ihantola's research with the plagiarism prevention method has several shortcomings, namely ignoring the process of work so that students can be cheated by buying assignments, the analysis at the end makes students able to cheat during assignments, no any log produced so the teacher can't assess student effort, and the software is tied to a particular platform. This research aims to perfect previous research by adding a snapshotting process that records document changes, user activity logging which records student activities, and build the systems with agnostic properties so that there is freedom to choose the form of tasks and the software that will be used. The system is tested using unit testing, integration, validation, automated testing, and compatibility. Unit testing and integration are valid and exceed 70% code coverage, validation testing in 32 test cases are valid, and compatibility testing shows the system is running well on six common desktop environments. Valid automated testing that contains no errors can speed up the testing process.